2005
DOI: 10.1029/2004gl021964
|View full text |Cite
|
Sign up to set email alerts
|

External fields on the nightside of Mars at Mars Global Surveyor mapping altitudes

Abstract: [1] More than four years of data taken from Mars Global Surveyor during its Mapping Phase Orbits (360-420 km altitude) over low field regions were examined. The nightside magnetic field data were binned according to a proxy solar wind pressure calculated from the dayside measurements. When the crustal field contribution calculated from the internal field model (FSU90) is removed, the distribution of residuals is bi-valued in the sunward component. Pass-by-pass inspections of the data sometimes show a sudden re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 20 publications
5
39
1
Order By: Relevance
“…Comparison of MGS premapping MPB crossings to a model for the boundary shape by Verigin et al (2004) suggests that crustal magnetic fields act to make the tail boundary (the nightside extension of the MPB) thicker by up to 1000 km, so that both intrinsic and induced fields influence the tail structure. MGS mapping data revealed a magnetic flux asymmetry between the two lobes of the induced magnetotail (Ferguson et al, 2005). More detailed study of nightside current sheet crossings (inferred from field reversals) shows that the thin current sheets measured at the 400 km mapping altitude of MGS (shown in Figure 12) have locations and variability consistent with reconnection of the draped IMF to crustal magnetic fields .…”
Section: Wakementioning
confidence: 78%
See 3 more Smart Citations
“…Comparison of MGS premapping MPB crossings to a model for the boundary shape by Verigin et al (2004) suggests that crustal magnetic fields act to make the tail boundary (the nightside extension of the MPB) thicker by up to 1000 km, so that both intrinsic and induced fields influence the tail structure. MGS mapping data revealed a magnetic flux asymmetry between the two lobes of the induced magnetotail (Ferguson et al, 2005). More detailed study of nightside current sheet crossings (inferred from field reversals) shows that the thin current sheets measured at the 400 km mapping altitude of MGS (shown in Figure 12) have locations and variability consistent with reconnection of the draped IMF to crustal magnetic fields .…”
Section: Wakementioning
confidence: 78%
“…Therefore, a negative net flux at the 2am orbit may be compensated by a net positive flux at other local times. Ferguson et al (2005) also observed an asymmetry in the sunward component of the nightside magnetic field, after a spherical harmonic crustal field model was subtracted (see Figure 16). Further, the asymmetry between the number of observations with B toward the Sun/planet vs. away grew with upstream solar wind pressure.…”
Section: Asymmetriesmentioning
confidence: 84%
See 2 more Smart Citations
“…It contains the night side plasma sheet (Dubinin et al, 1991;Ferguson et al, 2005), a steady outflow of escaping oxygen ions (Kallio et al, 1995), and is the region used as the primary source of information about unperturbed crustal magnetic fields, since external fields are weaker and the plasma environment is less turbulent than the day side . While external fields are nearly entirely horizontal on the day side of Mars, the radial field component comprises a larger fraction of the total field on the night side in MGS data (Brain et al, 2003).…”
Section: Night Side Vertical Magnetic Fieldsmentioning
confidence: 99%